2016
DOI: 10.3389/fnins.2016.00493
|View full text |Cite
|
Sign up to set email alerts
|

A Mouse Model for Binge-Level Methamphetamine Use

Abstract: Binge/crash cycles of methamphetamine (MA) use are frequently reported by individuals suffering from MA use disorders. A MA binge is self-reported as multiple daily doses that commonly accumulate to 800 mg/day (~10 mg/kg/day for a 170 pound human). A genetic animal model with a similar vulnerability to binge-level MA intake is missing. We used selectively bred MA high drinking (MAHDR) and low drinking (MALDR) mouse lines to determine whether several procedural variations would result in binge-level MA intake. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
50
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(52 citation statements)
references
References 42 publications
2
50
0
Order By: Relevance
“…Initially developed as an animal model of differential genetic risk for MA intake, mice were bidirectionally selectively bred for voluntary MA consumption from the F2 cross of C57BL/6J (B6) and DBA2/J (D2) mice, using a two-bottle choice task, generating the MA high drinking (MAHDR) and MA low drinking (MALDR) lines (Wheeler et al , 2009). It was later discovered that D2 mice possess a non-synonymous single-nucleotide polymorphism (SNP) that encodes a present, but non-functional TAAR1 and MAHDR mice were homozygous for the D2 allele, whereas MALDR mice were either hetero- or homozygous for the dominant B6 allele that encodes a functional TAAR1 (Harkness et al , 2015;Shabani et al , 2016). Besides differential MA consumption, MAHDR mice expressing the non-functional D2 Taar1 allele exhibit MA-conditioned place preference (CPP), but are insensitive to MA-conditioned taste aversion (CTA), whereas MALDR mice expressing the functional B6 allele lack MA-induced CPP and exhibit high sensitivity to MA-induced CTA (Wheeler et al , 2009;Shabani et al , 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Initially developed as an animal model of differential genetic risk for MA intake, mice were bidirectionally selectively bred for voluntary MA consumption from the F2 cross of C57BL/6J (B6) and DBA2/J (D2) mice, using a two-bottle choice task, generating the MA high drinking (MAHDR) and MA low drinking (MALDR) lines (Wheeler et al , 2009). It was later discovered that D2 mice possess a non-synonymous single-nucleotide polymorphism (SNP) that encodes a present, but non-functional TAAR1 and MAHDR mice were homozygous for the D2 allele, whereas MALDR mice were either hetero- or homozygous for the dominant B6 allele that encodes a functional TAAR1 (Harkness et al , 2015;Shabani et al , 2016). Besides differential MA consumption, MAHDR mice expressing the non-functional D2 Taar1 allele exhibit MA-conditioned place preference (CPP), but are insensitive to MA-conditioned taste aversion (CTA), whereas MALDR mice expressing the functional B6 allele lack MA-induced CPP and exhibit high sensitivity to MA-induced CTA (Wheeler et al , 2009;Shabani et al , 2012).…”
Section: Discussionmentioning
confidence: 99%
“…6,11,12 MA has dose-dependent negative subjective effects such as anxiety and dysphoria, particularly after 2 to 3 days of abstinence. 20 Furthermore, MA intake was sustained in MAHDR mice after each of several forced abstinence periods of 30 hours in duration. [14][15][16] Unknown is the relationship between the magnitude of symptoms occurring after MA is withdrawn and genetic risk for MA consumption.…”
mentioning
confidence: 96%
“…13 Sensitivity to initial positive psychostimulant drug effects has some predictive value for future intake in human and nonhuman subjects. 20 One of the two progenitors of the selected lines, the DBA/2J (D2) strain, but not the other progenitor, the C57BL/6J (B6) strain, voluntarily consumes MA. However, greater sensitivity to the initial negative subjective effects of MA may reduce subsequent MA use in humans, 14 and greater sensitivity to conditioned aversive effects of MA is genetically associated with reduced MA intake in mice.…”
mentioning
confidence: 99%
“…Plasma levels of CCL3 had not recovered as long as 6 months after MA abuse, though a within-subject examination of CCL3 levels during recovery from MA abuse is needed. Our studies using a different animal model (low-dose MA treatment) found an increase in plasma and hippocampal CCL3 within 72 h of MA treatment and recovery of CCL3 levels after 3 weeks of abstinence [57]; however, it would be exciting to study this in our model of binge-level voluntary MA use [11]. In previous work, 4 h after a single 2 mg/kg dose of MA, the oppositely selectively bred low MA drinking MALDR mice exhibited reduced expression of ccl3 in the nucleus accumbens, as compared to saline-treated MALDR mice [18].…”
Section: Discussionmentioning
confidence: 99%
“…MAHDR mice voluntarily consume MA in a 2-bottle choice procedure and operantly self-administer MA orally and intracerebroventricularly to a larger extent than MA low drinking (MALDR) mice [10]. Furthermore, the MAHDR line consumes binge-like levels of MA under conditions of high MA availability [11], making them a good model for human MA addiction.…”
Section: Introductionmentioning
confidence: 99%